Juvenile probation officer cynicism - Rush, Jeffrey P. (American journal of criminal justice, 1991)
This article addresses the question of cynicism among juvenile probation officers in Alabama. The findings reveal that Alabama juvenile probation officers are not as cynical as police and correctional officers have been found to be. It also reports that Alabama juvenile probation officer cynicism cannot be explained by the demographic variables of sex, length of service, and age.